X-linked hypohidrotic ectodermal dysplasia in the newborn: a diagnostic challenge. - Taieb, A. (European Journal of Pediatric Dermatology, 1998)
X-linked hypohidrotic ectodermal dysplasia is the most common phenotype in the group of ectodermal dysplasia. It is characterized by hypohidrosis, hypodontia and hypotrichosis. The Author underlines the need for an early diagnosis, namely in the neonatal period, of this disorder. The latter is in fact particularly dangerous in this period, when not recognized, due to the impaired thermolysis, unfortunately, the most characteristic signs of the disorder, namely hypotrichosis and hypodontia, are not obvious at this age. Therefore, the diagnosis should be suspected at this age in case of minor signs such as unexplained fever, collodion-like membranes, prominent forehead, periorbital darkening and saddle nose in a male infant. The carrier mother usually presents minor dental and hair problems.